Inheritance of deleterious mutations at both BRCA1 and BRCA2 in an international sample of 32, 295 women. Issue 1 (December 2016) - Rebbeck, Timothy; Friebel, Tara; Mitra, Nandita; Wan, Fei; Chen, Stephanie; Andrulis, Irene; Apostolou, Paraskevi; Arnold, Norbert; Arun, Banu; Barrowdale, Daniel; Benitez, Javier; Berger, Raanan; et al.
Abstract Background MostBRCA1 orBRCA2 mutation carriers have inherited a single (heterozygous) mutation. Transheterozygotes (TH) who have inherited deleterious mutations in bothBRCA1 andBRCA2 are rare, and the consequences of transheterozygosity are poorly understood. Methods From 32, 295 femaleBRCA1/2 mutation carriers, we identified 93 TH (0.3 %). "Cases" were defined as TH, and "controls" were single mutations atBRCA1 (SH1) orBRCA2 (SH2). Matched SH1 "controls" carried a BRCA1 mutation found in the TH "case". Matched SH2 "controls" carried a BRCA2 mutation found in the TH "case". After matching the TH carriers with SH1 or SH2, 91 TH were matched to 9316 SH1, and 89 TH were matched to 3370 SH2. Results The majority of TH (45.2 %) involved the three common Jewish mutations. TH were more likely than SH1 and SH2 women to have been ever diagnosed with breast cancer (BC;p = 0.002). TH were more likely to be diagnosed with ovarian cancer (OC) than SH2 (p = 0.017), but not SH1. Age at BC diagnosis was the same in TH vs. SH1 (p = 0.231), but was on average 4.5 years younger in TH than in SH2 (p < 0.001). BC in TH was more likely to be estrogen receptor (ER) positive (p = 0.010) or progesterone receptor (PR) positive (p = 0.013) than in SH1, but less likely to be ER positive (p < 0.001) or PR positive (p = 0.012) than SH2. Among 15 tumors from TH patients, there was no clear pattern of loss of heterozygosity (LOH) forBRCA1 orBRCA2 in either BC or OC. Conclusions Our observations suggest that clinical TH phenotypes resemble SH1. However, TH breast tumor marker characteristics are phenotypically intermediate to SH1 and SH2.